PENGARUH DANA PERIMBANGAN DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP PERTUMBUHAN EKONOMI MELALUI BELANJA MODAL DI KOTA MALANG (TAHUN 2011-2016) - Selamet Riadei Siahaan (Parsimonia - Jurnal Ekonomi dan Bisnis, 2018)
The management of regional finance is important to support the achievement of development and the welfare of its people. The government should effectively streamline local revenue sources and make budget absorption efforts with the right allocations. The purpose of this study is to analyze the influence of Local Original Income (PAD), balance funds and capital spending on economic growth Malang City period 2010-2016. This type of research is quantitative causal research. The data used are secondary data in the form of financial reports related to PAD, Capital Expenditure, Balancing Fund and Report of economic growth of Malang City in the period 2011-2016. Data analysis technique used is multiple regression. The result of the research shows that (1) PAD has significant effect to economic growth, (2) balancing fund has no significant effect to economic growth, (3) capital expenditure has no significant effect on economic growth, (4) PAD, Balancing Fund and Capital Expenditure Significant to economic growth.